Propuesta de mejora para la eficiencia productiva en las empresas textiles de la provincia Sullana-Piura - Guerrero Mena, Anais (2024)
Productive efficiency is a key factor for the success of companies, especially in textile companies, which currently enjoy different advantages. The main objective of this study was to evaluate a proposal to improve productive efficiency in textile companies in the province of Sullana - Piura. The research was applied, with a non-experimental design and an explanatory level. In this research we worked with a company of the province according to our experience. Also, a mathematical modeling was carried out to find the productive efficiency of the company, which showed that the company has a positive productive efficiency in relation to two garments. Finally, it was concluded that the implementation of the improvement proposal will have a significant impact on the productive efficiency of the companies in the province of Sullana.